The Efficacy Of Encapsulated Castor (Ricinus communis) Leaf Extract Against Colletotrichum Sp. Causing Antracnose In Curly Red Chili - Ratu Angkasawati Purboyo; Danar Wicaksono (Universitas Wiralodra, 2026)
Anthracnose disease, which attacks curly red chili, can be controlled with botanical plant extract pesticides; however, the liquid formulation is easily degraded, reducing its effectiveness. This study evaluated the efficacy of encapsulated Castor leaf extract against Colletotrichum sp. on curly red chili. The research was conducted from February to July 2025 at the Plant Protection Laboratory, Faculty of Agriculture, UPN “Veteran” Yogyakarta, and the encapsulation process was carried out at Pusat Studi Pangan dan Gizi Universitas Gadjah Mada. The method used was a completely randomized design, both in vitro and in vivo, with six treatments. Observation parameters included fungal colony diameter, percentage of inhibition, disease incidence, disease severity, Area Under the Disease Development Curve, and pesticide effectiveness. Observation data were analyzed using Analysis of Variance and followed by the Orthogonal Contrast Test at 5% significance level. In vitro assays demonstrated the highest effectiveness of the non-encapsulated extract at 1%. In contrast, in vivo evaluations showed that the encapsulated castor leaf extractdid not show a significant difference compared to the non-encapsulated extract in vivo . The efficacy of the 0.5% encapsulated extract was still lower than that of the synthetic fungicide Propineb 70%, yet it demonstrated considerable potential as an alternative for managing anthracnose in curly red chili.